1991
DOI: 10.1159/000226922
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carotenoid Administration on Bladder Cancer Prevention

Abstract: Bladder cancer was induced in male B6D2F1 strain mice by the administration of N-butyl-N-(4-hydroxybutyl)nitrosamine. Mice supplemented with β-carotene for 5 weeks before receiving the carcinogen and maintained on β-carotene for an additional 26 weeks developed significantly fewer tumors than did unsupplemented mice. Mice receiving canthaxanthin for the same time period showed no protection against the development of bladder cancer. effect of this molecule must be an intrinsic property of carotenoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 12 publications
0
10
1
Order By: Relevance
“…Some studies reported a significant inverse association between intake of carrots and dark green vegetables and the risk of bladder cancer (3,6,8,40,41). Against expectation, we did not find significant negative associations of intakes of cabbage, lettuce, green leafy vegetables, carrots, squash, or tomatoes with the risk of urothelial cancer death.…”
Section: Discussioncontrasting
confidence: 84%
“…Some studies reported a significant inverse association between intake of carrots and dark green vegetables and the risk of bladder cancer (3,6,8,40,41). Against expectation, we did not find significant negative associations of intakes of cabbage, lettuce, green leafy vegetables, carrots, squash, or tomatoes with the risk of urothelial cancer death.…”
Section: Discussioncontrasting
confidence: 84%
“…Animal studies evaluating the chemopreventive effects of retinoids have found that a range of synthetic and naturally occurring retinoids inhibit chemically induced bladder carcinogenesis in rats and mice (5)(6)(7)55). Furthermore, in human studies, serum vitamin A levels were shown to be lower in patients with bladder cancer (4), whereas a reduced incidence of bladder cancer was noted in patients with a high dietary intake of vitamin A or carotenoids (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A (retinol; ROL) levels have been shown to be significantly lower in the serum of patients with bladder cancer when compared with controls (4). Moreover, previous studies have demonstrated that retinoids were effective in preventing chemically induced bladder cancer in rats (5) and mice (6,7). The effects of retinoids on growth inhibition of TCC have also been demonstrated in vitro in several human bladder cancer cell lines (8 -10).…”
Section: Introductionmentioning
confidence: 99%
“…In certain non-photosynthetic organs of plants, such as some ripening fruits, carotenoids accumulate in large amounts in chromoplasts [3] and are involved in the attraction of animals which will facilitate pollination or seed dispersal. In mammals, certain carotenoids such as fl-carotene, are precursors of vitamin A, retinoic acid and retinal, and have been proposed to act as anti-cancer agents [4].…”
Section: Introductionmentioning
confidence: 99%